Pentingnya penggunaan Aedes aegypti (Diptera: Culicidae) strain rentan insektisida serta kandang ukuran tertentu dalam uji efikasi insektisida aerosol - Andreas D. Advento; Intan Ahmad; Nova Hariani; Resti Rahayu (Fakultas Biologi | Universitas Jenderal Soedirman, 2012)
Before insecticide formulations can be registered and commercialized, efficacy of the insecticide should be carried out by an independent institution such us universities or research institutes. Based on the available protocol issued by the Pesticide Committee, we tested the efficacy two aerosol insecticides i.e. Baygon® and HIT® on Jakarta strain, Bandung strain, and Surabaya strain of Aedes aegypti, including the VCRU standard susceptible strain, confined in two cages with different dimensions inside the Peet-Grady chamber. The findings show that each of the four strains of Aedes aegypti had a significantly different KT50 value after being exposed to Baygon® and HIT® with the VCRU strain had the fastest KT50 among other strains.The results also show that all strain of Aedes aegypti tended to have higher KT50 (knockdown time 50%) when treated inside the large cage (30x30x30 cm) than those in the smaller cage (15x15x15 cm) even though treated with the same insecticide. The finding of this research suggests that it is imperative that the design and the protocol of insecticide efficacy test issued by the Pesticide Committee should state clearly the strain of Aedes aegypti being used as well as the dimension of the cage inside the Peet-Grady chamber. Herewith we suggest that standard insecticide susceptible Aedes aegypti strains such as VCRU as well as 15 X 15 X 15 cm cage are to be used for the mosquito aerosol efficacy test in the Peet-Grady chamber.